The strategic likelihood forecast of ecologo-economic development of Kazakhstan. (Journal of Geography and Environmental Management, 2016)
Factors of strategic matrix of Kazakhstan are considered and estimation of contribution components in state development is given. It is offered to consider risks of destabilization system at a complex estimation of interactionobjects of the natural, social, economic environment.